Fertirrigação na produção de mudas de Eucalyptus grandis nos períodos de inverno e verão - Ciavatta, Simone Fernandes [UNESP]; Silva, Magali Ribeiro da [UNESP]; Simões, Danilo [UNESP] (Univ Federal Lavras-ufla, 2014)
Studies correlating the splitting of fertigation with the development and quality of tree seedlings in different production systems and periods of the year are fundamental to optimize inputs and minimization of the production cycle. Thus we conducted this study aimed to check the influence of the split of fertigation in the development and quality of Eucalyptus grandis seedlings in winter and summer periods. The fertilization through the irrigation system by capillarity was split on: one, two, three or six times in the week, maintaining the total amount of nutrients applied. We concluded that the most effective fertigation for the development and quality of seedlings of Eucalyptus grandis were six and one times in the week for the period of winter and summer, respectively, demonstrating the need for adequacy of fertigation managements according to the period of year.

Pesquisas correlacionando o parcelamento da fertirrigação com o desenvolvimento e qualidade de mudas florestais, em diferentes sistemas de produção e períodos do ano são fundamentais para a otimização de insumos e minimização do ciclo de produção. Dessa forma conduziu-se esse estudo com o objetivo de verificar a influência do parcelamento da fertirrigação no desenvolvimento e qualidade de mudas de Eucalyptus grandis nos períodos de inverno e verão. As fertilizações por meio do sistema de irrigação por capilaridade foram parceladas em: uma, duas, três ou seis vezes por semana, sendo mantida a quantidade total de nutrientes aplicados. Concluiu-se que, as fertirrigações mais eficazes para o desenvolvimento e a qualidade de mudas de Eucalyptus grandis foram de seis e uma vez na semana, para o período de inverno e verão, respectivamente, demonstrando-se a necessidade de adequação dos manejos de fertirrigação em função do período do ano.
Fertirrigation in production of seedlings of Eucalyptus grandis during winter and summer
Keywords: Forest nursery; Fertilization; Eucalypt; Splitting of fertilizer; Viveiro florestal; Adubação; Eucalipto; Parcelamento de fertilizantes